Bio-grouting technologies for enhancing uniformity of biocementation: A review - Junjie Zheng; Hanjiang Lai; Mingjuan Cui; Xingzhi Ding; Yajie Weng; Jianwei Zhang (Biogeotechnics)
Biocementation-based soil improvement is an emerging ground treatment method in geotechnical engineering that has garnered extensive attention over the past two decades. One of the challenges associated with this method revolves around the uniformity of biocementation, a crucial factor closely tied to bio-grouting technology. The traditional biotreatment methods, the two-phase method and the one-phase method, suffer from the issue of non-uniform biocementation. Consequently, in recent years, various improved grouting technologies have been proposed to address this concern by aiding bacterial adsorption and controlling carbonate precipitation. This paper reviews the mechanisms and grouting processes employed in these enhanced bio-grouting technologies. Additionally, the challenges of implementing these grouting technologies in real-world applications are also thoroughly discussed.